Efecto de la aplicación de dos tipos de fertilizantes sobre el comportamiento agronómico del girasol (Helianthus annuus), en la zona de San Juan - Chica Contreras, Griselda Dayana (2018)
VIII. SUMMARY The present experimental work entitled: "Effect of the application of two types of fertilizers on the agronomic behavior of sunflower (Helianthus annuus), in the San Juan area". It was carried out in the area of San Juan, located on the Pan-American San Juan - Puebloviejo road, 3 km inside the San Pedro de Valdivia enclosure on the estate of Ms. Urbana Chica. The area has a humid tropical climate with an average annual temperature of 26.2 ° C, an annual rainfall of 2656 mm, relative humidity of 76%, daily heliophone 3.5 hours light. The geographic coordinates are UTM East X = 657750,6664 and UTM North Y = 9832573,201. Testing two types of fertilization: conventional fertilization Urea (46% N), Diammonium Phosphate (18% N, 46% P2O5), Potassium muriate (60% K2O), Magnesium Sulfate (25% MgO + 20% S), and Controlled release fertilization with a Basacote Plus product (16% N, 8% P, 12% K + 2% MgO). This work was carried out in order to: a) Evaluate the agronomic behavior of the sunflower crop under three types of chemical fertilizers. b) Know the agronomic behavior and yield of sunflower to two chemical fertilizer formulas. c) Identify the most appropriate fertilizer to maximize sunflower production. d) Carry out an economic analysis of the treatments under study. The design "Complete blocks at random" was used. In four repetitions; each block consisted of five treatments randomly distributed. Each experimental plot had an area of 4.00 m wide and 3.00 m long, the useful area of each experimental plot was determined by three central rows, eliminating a row on each side by edge effect, the dental row was of 1.00 m. The variables were evaluated: plant height, stem diameter, leaf area, number of leaves per plant, diameter of the floral chapter, grains per chapter, weight of the chapter, weight of 100 seeds and grain yield. For comparison and adjustments of means of treatments, the Tukey test was used at 95% probability. From the analysis of the experimental results and discussion of them, the following was concluded: The application of conventional fertilizer stimulates a higher production of seeds per chapter in the sunflower plant in relation to the treatments with controlled release fertilizer. The Basacote plus fertilizer in a dose of 200 kg / ha contributes to a better weight of 100 seeds per chapter in relation to the other treatments. The treatment with conventional fertilizer obtained the highest performance record kg / ha within this study. It is recommended: Perform similar investigations with other planting materials, fertilizer sources and under other environmental conditions. Use conventional fertilizer, since this yields good yields and its cost is lower compared to controlled release fertilizers. Use certified seeds for sowing so that production is greater, compared to the productions obtained with artisanal seed.